Control over the Self‐Assembly Modes of PtII Complexes by Alkyl Chain Variation: From Slipped to Parallel π‐Stacks. Issue 23 (26th April 2016) - Allampally, Naveen Kumar; Mayoral, María José; Chansai, Sarayute; Lagunas, María Cristina; Hardacre, Christopher; Stepanenko, Vladimir; Albuquerque, Rodrigo Q.; Fernández, Gustavo
Abstract: We report the self‐assembly of a new family of hydrophobic, bis(pyridyl) Pt II complexes featuring an extended oligophenyleneethynylene‐derived π‐surface appended with six long (dodecyloxy (2 )) or short (methoxy (3 )) side groups. Complex2, containing dodecyloxy chains, forms fibrous assemblies with a slipped arrangement of the monomer units (dPt⋅⋅⋅Pt ≈14 Å) in both nonpolar solvents and the solid state. Dispersion‐corrected PM6 calculations suggest that this organization is driven by cooperative π–π, C−H⋅⋅⋅Cl and π–Pt interactions, which is supported by EXAFS and 2D NMR spectroscopic analysis. In contrast, nearly parallel π‐stacks (dPt⋅⋅⋅Pt ≈4.4 Å) stabilized by multiple π–π and C−H⋅⋅⋅Cl contacts are obtained in the crystalline state for3 lacking long side chains, as shown by X‐ray analysis and PM6 calculations. Our results reveal not only the key role of alkyl chain length in controlling self‐assembly modes but also show the relevance of Pt‐bound chlorine ligands as new supramolecular synthons. Abstract : Weak but significant : The absence or presence of long alkyl side groups (methoxy vs. dodecyloxy) is found to govern the packing modes (parallel vs. slipped stacks) of hydrophobic bis(pyridyl) Pt II complexes featuring an extended π‐surface (see figure). Unconventional weak interactions involving metal‐polarized chlorine groups have thereby established themselves as new synthons in the field of supramolecular chemistry.